FAKTOR-ÂFAKTOR YANG MEMPENGARUHI KEMATIAN BAYI PREMATUR DI INDONESIA - Rizqiani, Ratu Fani; Yuliana, Lia (E-Journal Widya Kesehatan dan Lingkungan, 2018)
Incidence of premature is a major cause of premature death in infants aged less than one year. Indonesia is a country with the fifth highest number of premature babies in the world. Unlike the full-term babies, premature infants are the immaturity of organ systems that cause premature infants at high risk of various health problems and death. This study aims to determine the factors that influence a premature infant mortality in Indonesia. The data used in this research is secondary data from Riskesdas 2013. The analytical method used is descriptive and inferential analysis in the form of binary logistic regression. The results showed that: 1) with a significance level of 5 percent, the type of region, type of birth, gestational age, and birth complications significantly affect the mortality of premature babies; 2) Premature babies of mothers who live in urban areas, were born twins, born with a gestational age less than 32 weeks, and born to mothers who experience delivery complications have a higher tendency to experience death; 3) In an effort to reduce infant mortality, the Government is expected to improve the quality of health services and provide convenience to pregnant women in accessing health services.